Hubungan Antara Efikasi Diri dalam Mengajar dengan Tingkat Stres pada Guru Anak Berkebutuhan Khusus di Yayasan Matahari Banyuwangi - Nisa, Adinda Ayu; Fitri, Arrumaisha (Fakultas Dakwah UIN KHAS Jember, 2024)
This research is motivated by the importance of education for children with special needs (ABK). Being an ABK teacher is one of the most challenging and stressful jobs in the world of education. The various demands of being an ABK teacher also become obstacles in completing the tasks of being a ABK teacher. This is also felt by ABK teachers at the Matahari Banyuawangi Foundation. This will make teachers potentially experience work stress if they do not have self-confidence in their ability to complete their roles and be assigned. Confidence in one's abilities will lead to a greater feeling of internal control over the work one does. So that self-efficacy possessed by teachers is an important role in reducing work stress faced, with high self-efficacy individuals will have a strong feeling or belief in being able to complete certain tasks, so that individuals will be able to carry out various efforts to achieve goals and hopes of becoming a special needs teacher at the Matahari Banyuawangi Foundation. This research aims to determine the relationship between self-efficacy in teaching and stress levels in teachers of children with special needs at the Matahahari Banyuwangi Foundation. This research uses a quantitative approach with a correlation type. Researchers used the entire population and the testing strategy used was the saturated sampling method. The data collection technique in this research used a questionnaire. The instrument in this research uses two scales, namely the self-efficacy scale and the stress level scale. This scale has gone through a validity test with the overall item result being r count > r table (r table of 0.361 for ???? = 5%) and also through a reliability test with Cronbach's Alpha results >0.60. The data analysis technique used is the Pearson product moment correlation test. The correlation test carried out obtained a significance value of 0.000<0.05. The r value obtained was 0.831. Self-efficacy in this study contributed 83.1% to stress levels and the remaining 16.9% was influenced by factors other than the variables examined in the research. In conclusion, the hypothesis proposed by researchers in this study can be accepted, namely that there is a significant relationship between self-efficacy in teaching and stress levels in teachers of children with special needs at the Matahari Banyuwangi Foundation.